Covalent Organic Frameworks for Biomedical Applications. Issue 6 (21st January 2021) - Esrafili, Arezoo; Wagner, Avery; Inamdar, Sahil; Acharya, Abhinav P.
Abstract: Covalent organic frameworks (COFs) are porous organic polymeric materials that are composed of organic elements and linked together by the thermodynamically stable covalent bonds. The applications of COFs in energy sector and drug delivery are afforded because of the desirable properties of COFs, such as high stability, low density, large surface area, multidimensionality, porosity, and high‐ordered crystalline structure expanded. In this review COFs are reviewed, from the perspective of different types of reported COFs, different methods for their synthesis, and their potential applications in the biomedical field. The main goal of this review is to introduce COFs as a biomaterial and to identify specific advantages of different types of COFs that can be exploited for specialized biomedical applications, such as immune engineering. Abstract : This paper provides a review of synthesis, characterization, and application of covalent organic frameworks (COFs). Moreover, this review also discusses potential new research directions of COFs in biomedical applications.